Computational modeling of the tissue mechanics in rheumatic heart disease patients - Familusi, Mary Ajibola (Department of Civil Engineering, 2025)
Non-invasive measurements play a crucial role in advancing heart failure treatments, a leading global cause of mortality. Understanding the biomechanical characteristics of myocardial material behavior in both healthy and diseased hearts through finite element analysis offers valuable insights into cardiac function and potential interventions for diastolic abnormalities linked to ventricular hypertrophy and inflammation. This study aims to develop accurate, subject-specific computational models of the human bi-ventricle using high-resolution cardiovascular magnetic resonance (CMR) images from rheumatic heart disease patients (RHD) and healthy individuals. These models will facilitate the investigation of heart biomechanics, focusing on the impact of myocardial elastic material behavior, including compliance (stiffness), muscle fiber orientation angles, and directionally dependent properties (anisotropy coefficients). Using CMR images, three-dimensional (3D) finite element models (FEM) were constructed for both RHD patients and healthy subjects. The material parameter optimization uses inverse modeling based on the finite element method combined with the Levenberg-Marquardt method (LVM) by targeting subject-specific hemodynamics. The computational models describe the passive behavior of the myocardium by nonlinear, orthotropic, and nearly incompressible hyperelastic material constitutive equations. Parameter optimization of myocardial tissue stiffness, anisotropy coefficients, fiber angles, and diastolic pressures aimed to minimize the error between the Klotz curve and the simulated end-diastolic pressure-volume relationship (EDPVR) curve for each subject. Beginning with the unloaded left ventricular volume (V0), optimization progressed until the end-diastolic volume (EDV) was reached at the specified end-diastolic pressure (EDP). Objective functions were defined based on the difference between simulated and measured left ventricle (LV) and right ventricle (RV) EDVs. Additionally, two further objective functions were established: the first combining EDVs and global strains (circumferential, longitudinal, and radial), and the second combining EDVs with short-axis diameters. The study of elastic myocardial parameters between healthy subjects and RHD patients shows an elevated stiffness in diseased hearts. In particular, the anisotropic material behavior of the healthy and diseased cardiac tissue significantly differs. Furthermore, as the left ventricular ejection fraction (LVEF) decreases, the myocardial tissue stiffness and anisotropy coefficients increase. The LV myocardial circumferential and longitudinal stresses were negatively associated with LVEF. The sensitivity analysis results demonstrate that the observed significant difference between the elastic material parameters of diseased and healthy myocardium is not exclusively attributable to increased left ventricular end-diastolic pressure (LVEDP) in the diseased heart, but rather to the presence of fibrosis in the myocardium. Additionally, the sensitivity of elastic material parameters and muscle fiber angles with respect to the specific strain components included as targets in the objective function was reported on. Patient-specific computer simulations of EDV and strains for all objective functions agreed well with clinical data. The error difference between the predicted and clinical parameters is less than 0.1%. Qualitative and quantitative differences in stress and strain distributions for each parameter optimization target are presented. Lastly, the combination of EDV and cavity diameters to estimate elastic material parameters, fiber angles, and diastolic pressures was explored. The obtained results distinguish between the elastic material parameters and diastolic pressures of individuals with RHD and those of healthy controls. The study provides valuable insights into the biomechanical characteristics of the myocardium, advancing our understanding of cardiac function in health and disease and offering potential implications for clinical practice and future research directions.